Value Chain Analysis In The Marble Production Process In Aceh Selatan Polytechnic. - Afdhal, Afdhal; Sastra, Hasan Yudhie; Husni, Husni (Information Technology and Science (ITScience), 2024)
Potential rocks such as granite and marble are easy to find in mining products in South Aceh. South Aceh granite and marble, which have high quality, provide benefits and have great potential to be developed. Currently, the use of marble is made into various crafts carried out by workshop the South Aceh PolytechnicCurrent market competition requires a value-added from a product, so the purpose of this study is to conduct a supply chain analysis in the marble production process at the South Aceh Polytechnic. Increasing value chain to marble products is expected to contribute to business development significantly. This research focused on the plan and source stages. The results found that activities in marble production at the South Aceh Polytechnic lack agreements with third parties as both marble supply agents and cooperation agreements with packaging companies, so the marble handicrafts produced have not produced a product. Ready to compete in the market.